The Conditions for Journalism Freedom and the Invisible Threat to Free Speech - Pilotta, Joseph J. (Žurnalistikos tyrimai, 2015)
Political communication is strictly distinguished from social and individual activities that are interest-laden and thus lack the autonomy to be political. The latter belongs solely to political societies that are democratic. Indeed, there must be a strict restriction of the use of political to a public domain in which every member of society participates in public debates and decisions. Participation in debate and decision-making requires the gemini of communication: understanding and accessibility which require a public domain of public expression. The politics of technocratic journalism is the invisible threat to the right to freedom of speech.